An Immersive Memory Game as a Cognitive Exercise for Elderly Users - Farias, Flávio M. de; Montevecchi, Eyre; Bokehi, José Raphael; Santana, Rosimere F.; Muchaluat-Saade, Débora Christina (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2022: Proceedings of the 2nd Life Improvement in Quality by Ubiquitous Experiences WorkshopDO - 10.5753/lique.2022.19997, 2022)
In the healthcare field, games and gamification have been applied as tools to support traditional treatments for dementia, anxiety, and depression. Immersive environments using Virtual Reality (VR) can help elderly users be more focused on the tasks to be done, enhancing their memory skills. This paper proposes a new cognitive exercise called Memo-VR, which combines VR technology with interaction techniques, such as scanning and virtualizing the user’s hands, to play a memory game. Memo-VR was evaluated with a group of elderly users who gave positive feedback about the game.